Skeletal development and adult osteology of Hypsiboas pulchellus (Anura: Hylidae) - Hoyos, Julio M. (2012)
Osteological and skeletal characters have long been proven to be particularlyinformative in taxonomic and systematic research. Furthermore, ossification sequencesare assumed to be a potential tool to investigate developmental states and developmentalmodes of fossil and extant skeletal specimens. Herein, we provide a detailed accounton adult osteology and skeletogenesis in the Montevideo treefrog, Hypsiboas pulchellus(Anura: Hylidae) based on evaluation of a series of cleared and stained specimens.A consensus sequence of ossification, i.e., the order of appearance of mineralized elementsuntil early metamorphosis could be determined as (parasphenoid, presacral vertebraeI-VII, frontoparietal, exoccipital) ? transverse processes of presacral vertebraeI-VIII ? sacral vertebra ? (humerus, radioulna, ilium, femur, tibiofibula, scapula) ?(cleithrum, clavicle, coracoids, metacarpals, tarsals, metatarsals, phalanges, hypochord)? (prootic, angulosplenial, dentary, maxilla, premaxilla, squamosal). Comparing thestate of mineralized elements in individual specimens, a number of skeletal elements,including the exoccipital, frontoparietal, parasphenoid and prootic, as well as elementsof the shoulder and pelvic girdles, and the phalanges, were found to vary intraspecificallyregarding the relative time of their ossification within the ossification sequence.